2022
DOI: 10.3389/fchem.2022.1017250
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling a family of spiro-β-lactams with anti-HIV and antiplasmodial activity via phosphine-catalyzed [3+2] annulation of 6-alkylidene-penicillanates and allenoates

Abstract: The molecular architecture of spirocyclic compounds has been widely explored within the medicinal chemistry field to obtain new compounds with singular three-dimensional pharmacophoric features and improved bioactivity. Herein, the synthesis of 68 new spirocyclopentene-β-lactams is described, resulting from a rational drug design and structural modulation of a highly promising lead compound BSS-730A, previously identified as having dual antimicrobial activity associated with a novel mechanism of action. Among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Spiro-β-lactams are a new class of compounds with potent (nM) activity against HIV-1 (mean IC 50 of the lead compound BSS-730A = 14 nM) [ 173 , 174 ]. More recently, we have shown that BSS-730A also has potent activity against primary HIV-2 isolates from INI-naïve patients (mean IC 50 = 18.10 nM) [ 131 ].…”
Section: Spiro-β-lactams Are Potent Inhibitors Of Hiv-2 Infectionmentioning
confidence: 99%
“…Spiro-β-lactams are a new class of compounds with potent (nM) activity against HIV-1 (mean IC 50 of the lead compound BSS-730A = 14 nM) [ 173 , 174 ]. More recently, we have shown that BSS-730A also has potent activity against primary HIV-2 isolates from INI-naïve patients (mean IC 50 = 18.10 nM) [ 131 ].…”
Section: Spiro-β-lactams Are Potent Inhibitors Of Hiv-2 Infectionmentioning
confidence: 99%